Pyridine compounds increase trap capture of Frankliniella occidentalis (Pergande) in a covered crop - Davidson, M.M.; Butler, R.C.; Winkler, S.; Teulon, D.A.J. (New Zealand Plant Protection, 2007)
The effect of pyridine compounds on the capture of thrips was examined in an Auckland New Zealand capsicum greenhouse in 2004 Yellow sticky traps were positioned just above the crop canopy in a rectangular array with 6 traps per compound and 6 control traps 2024 m apart and left for 24 h Most thrips found on traps were Frankliniella occidentalis (>99) Fourteen times more female F occidentalis were captured on traps with methyl isonicotinate or ethyl isonicotinate than on controls Sticky traps treated with methyl 4pyridyl ketone also caught more female F occidentalis than controls (45) Sticky traps with methyl isonicotinate caught more male F occidentalis (up to 52) than controls Ethyl2chloropyridine4carboxylate and ethyl nicotinate did not increase trap catches of either sex The results demonstrated that selected pyridine compounds have the potential to improve trap capture of F occidentalis in a covered crop